The Existence of The Jinayat Law in Indonesian Community [Eksistensi Hukum Jinayat dalam Masyarakat Nusantara] - Muhammad Yusuf (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2021)
Abstract: The struggle over the supremacy of Islamic law in the Indonesian archipelago began during the Dutch colonial period when the Dutch began to harass the community's laws to strengthen their grip on controlling the archipelago. Initially, Dutch legal scientists were still clear in seeing the truth that Islamic law in the Muslim community of the archipelago had a higher position than customary law so that the receptie in complex theory was born, but this did not last long because other Dutch legal scientists changed this theory with the receptie theory which puts law Islam is lower than customary law. This was done for the political interests of the Dutch power. After Indonesia's independence, Indonesian legal scientists began to realign the position of Islamic law and place it in its actual position, so that the receptie exit theory emerged which was pioneered by Hazairin, the theory of receptio a contrario by Sayuti Thalib, and the theory of existence by Ichtijanto. These three theories have the same goal, namely trying to place the position of Islamic law which is recognized for its existence in Indonesia. However, these theories do not fully apply in Indonesia because the jinayat (Islamic criminal) law has never received recognition as an enforceable law in Indonesia, but still uses the Dutch Criminal Code (KUHP). So, in this study, we want to see the extent of the existence of Islamic law in Indonesia and why jinayat law is very difficult to implement in Indonesia, where the majority of the population is Muslim. This study uses qualitative methods and library research (library research). The results of the study show that the existence of Islamic law in Indonesia is only in the civil field, while in the criminal field it is still using the KUHP inherited from the Netherlands, then the obstacles to the implementation of jinayat law are more on the culture of the people who are not fully following Islam and political constraints. Abstrak: Pergulatan tentang supremasi hukum Islam dalam masyarakat nusantara dimulai pada masa penjajahan Belanda, ketika Belanda mulai mengusik hukum masyarakat demi memperkuat cengkeramannya untuk menguasai bumi nusantara ini. Awalnya ilmuan hukum Belanda masih jernih dalam melihat kebenaran bahwa hukum Islam dalam masyarakat muslim nusantara lebih tinggi kedudukannya dari pada hukum adat sehingga lahir teori receptie in complexu, namun hal ini tidak berlaku lama karena ilmuan hukum Belanda lainnya merubah teori ini dengan teori receptie yang menempatkan hukum Islam lebih rendah dari hukum adat. Hal ini dilakukan untuk kepentingan politik kekuasaan Belanda. Setelah Indonesia merdeka, ilmuan hukum Indonesia mulai meluruskan kembali kedudukan hukum Islam dan menempatkannya pada kedudukan yang sebenarnya, sehingga muncul teori receptie exit yang dipelopori oleh Hazairin, teori receptio a contrario oleh Sayuti Thalib dan teori eksistensi oleh Ichtijanto. Ketiga teori ini mempunyai tujuan yang sama yaitu berusaha menempatkan kedudukan hukum Islam yang diakui eksistensinya di Indonesia. Namun tidak sepenuhnya teori-teori tersebut berlaku di Indonesia karena hukum jinayat (pidana Islam) tidak pernah mendapat pengakuan sebagai hukum yang dapat dilaksanakan di Indonesia, melainkan tetap masih menggunakan Kitab Undang-Undang Hukum Pidana (KUHP) peninggalan Belanda. Sehingga dalam penelitian ini ingin melihat sejauh mana eksistensi hukum Islam di Indonesia dan mengapa hukum jinayat sukar sekali dilaksanakan di Indonesia yang mayoritas penduduknya adalah umat Islam. Penelitian ini menggunakan metode kualitatif dan penelitian kepustakaan (library research). Hasil penelitian menunjukkan bahwa eksistensi hukum Islam di Indonesia hanya dalam bidang perdata, sementara dalam bidang pidana masih menggunakan KUHP peninggalan Belanda, kemudian kendala pelaksanaan hukum jinayat lebih kepada budaya masyarakat yang belum sepenuhnya sesuai dengan Islam dan kendala politik.